From Planning To Performing: Improving Critical Thinking Abilities Through The Implementation Of Understanding By Design - Mahesa Arifin; Heryanto Nur Muhammad; Muchamad Arif Al Ardha (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study aims to analyze the effectiveness of the implementation of the Understanding by Design (UbD) framework in improving students' critical thinking skills, especially in Physical Education and Health. The UbD approach, which is oriented towards learning objectives and authentic assessment, is hypothesized to create a learning environment that encourages analysis, evaluation, and synthesis of ideas. A quasi-experiment was used with a one-group pretest-posttest design. The study sample consisted of 32 students selected through the total sample method. A critical thinking ability questionnaire consisting of 17 validated statements was used to collect data. The results were analyzed using descriptive statistics and a Paired Sample T-Test with SPSS. The average score increased from 68.16 in the pretest to 74.69 in the posttest. There was a significant difference between critical thinking skills before and after the intervention, according to the statistical test, which produced a significance value (2-tailed) of 0.000 (p < 0.05). Therefore, it can be concluded that the use of the understanding by design framework has a positive and significant effect on improving students' critical thinking skills. The results show that UbD can be used as a pedagogical strategy to enhance higher-order thinking skills in education.